Proses kognitif mahasiswa calon guru matematika melalui penerapan metode kooperatif tipe guided note taking - Yuntawati, Yuntawati; Sanapiah, Sanapiah; Aziz, Lalu Abdul (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this study was to determine how the cognitive processes of prospective mathematics teacher students through the application of the Guided Note Taking method. The subjects of this study were the fifth semester students of the Mathematics Education Study Program, FSTT UNDIKMA. This type of research is descriptive analysis. Data collection techniques used are assignment and observation. The data analysis of this research describes each cognitive learning process starting from the process of acquiring new information, transforming the information received, and testing or developing the relevance and accuracy of knowledge. Based on the exposure of the research data, it can be said that the fifth semester students of the Mathematics Education Study Program are in the category or highest cognitive level, namely those who are able to absorb information and process it to the limit of application. Meanwhile, in cognitive processes, students are able to obtain information and information received, but have not been able to test and develop the relevance or accuracy of their knowledge